Embracing a New Day: Exploring the Connections of Culture, Masculinities, Bodies, and Health for Gay Men through Photovoice. (1st September 2021) - Joy, Phillip; Numer, Matthew; Kirk, Sara F. L.; Aston, Megan
Abstract: The construction of masculinities is an important component of the bodies and lives of gay men. The role of gay culture on body standards, body dissatisfaction, and the health of gay men was explored using poststructuralism and queer theory within an arts-based framework. Nine gay men were recruited within the city of Halifax, Nova Scotia, Canada. Participants were asked to photograph their beliefs, values, and practices relating to their bodies and food. Semi-structured interviews were conducted, using the photographs as guides. Data were analyzed by critical discourse analysis and resulted in three overarching threads of discourse including: (1) Muscles: The Bigger the Better, (2) The Silence of Hegemonic Masculinity, and (3) Embracing a New Day. Participants believed that challenging hegemonic masculinity was a way to work through body image tension.